#55: Development of a quality improvement educational intervention in febrile neutropenia in pediatric cancer patients in Peru: Preliminary results of the DoTT project. (28th June 2021) - Mendieta, Ana; Rios, Ligia; Delgadillo, Walter; Vargas, Maria; Rueda, Carlos; Santillán, Carlos; Vasquez, Liliana; Caniza, Miguela
Abstract: Background/Aims: Severe infections are the most important causes of morbidity and mortality in children with cancer. In Peru, a major limitation for an optimal treatment of children with fever and neutropenia due to chemotherapy is the delay in the administration of the first dose of antibiotics. We performed an intervention aimed to decrease the time to antibiotics (TTA) in pediatric patients presenting to the emergency room (ER) with fever and neutropenia: We increased the perception risk of neutropenic fever to the ER medical staff by explaining the importance of a timely administration of antibiotics as part of the initial approach of children with fever and neutropenia. This study forms part of a larger project (DoTT project) that is being implemented in Peru, and is aligned to the WHO Global Initiative of Childhood Cancer in Peru. Methods: This study was performed at Hospital Nacional Edgardo Rebagliati, which is a tertiary care National Hospital located in Lima. We included patients younger than 14 years with hemato-oncological conditions who arrived at the Pediatric Emergency Room. The DoTT project consists in an quality improvement educational intervention for health care providers in the Pediatric ED and the Oncology and Hematology Departments, based on the Kern's six-steps (i) Problem identification and general needs assessment, (ii) targeted needs assessment, (iii) goals and objectives, (iv) educational strategies, (v) implementation and (vi) evaluation. We defined time-to-antibiotic (TTA) by measuring the time elapsed between patient′s arrival to the ER and the administration of the fist dose of an antibiotic. We compared the TTA between thirteen patients admitted from July to December 2020 with fever and neutropenia (after intervention), and historical data from 2017–2018. Results: Median age was 7 years. 9/13 patients had leukemia and 4 patients had malignant solid tumors receiving oncological treatment. Mean pre-hospital delay was 176 minutes (range, 14–906 minutes) and TTA was 133 minutes (range, 34–400 minutes). One patient died of sepsis. Age, sex, source and timing of antibiotics did not significantly affect hospital stay, antifungal use and/or antibiotic turnover. Based on our historical data, mean TTA was 206 minutes (range, 137–390). Early results indicate a decrease in the TTA, although not statistically significant, likely due to the sample size. General and targeted needs assessment was performed by the DoTT project team and administrators at Rebagliati hospital, which lead to develop a curriculum based on a 5-lectures mini-course for health care providers. Conclusions: The TTA exceeds the recommended time at international level, causing the evitable morbimortality. It is necessary to perform a multidisciplinary intervention to improve antibiotic start time. Ongoing educational intervention refinement and testing of the instruments are planned.